Lopeg (Teacher Pedagogic Observation Sheet) : Development Of Instruments To Analyze The Feasibility Of Ukg Results In Sdn Percobaan Medan City - Rosmini, Paujia (Universitas Negeri Medan, 2017)
Ketua Umum PB PGRI Dr. Sulistiyo said